2D–shear-wave elastography example: non-MAFLD CKD case (male, 54 years). - Zienab M. Saad (22676502) (2025)
(A) Renal ultrasound shows average-sized kidneys with preserved parenchymal thickness but altered echogenicity and prominent papillae. (B) Liver 2D-SWE (LOGIQ S8 XDclear) with ROI placed 1.5–2.0 cm below the capsule, avoiding vessels and rib shadow. Average stiffness: 5.4 kPa (predominantly blue elastogram), consistent with no significant fibrosis (≤F1). (TIF)